Keabsahan Penarikan Paksa Kendaraan Bermotor Secara Sepihak Tanpa Sertifikat Fidusia - Triwulandari, Melsa; Kusuma, Ajeng Pramesthy Hardiani; Yasa, I Wayan (Acten Journal Law Review, 2025)
As stipulated in Article 11 of Law Number 42 of 1999 concerning Fiduciary Guarantees (UUJF), registration is required to obtain executory power. The case study of Decision Number 597/Pdt/2020/PT DKI shows that the withdrawal of a vehicle without a certificate is declared an unlawful act. This study aims to analyze the validity of such actions, the legal consequences they entail, and the remedies available to consumers. The methods used are normative legal research with a legislative and conceptual approach, as well as qualitative analysis based on literature review. The results of the study show that repossession without a Fiduciary Certificate is not legally valid because it contradicts Article 15 paragraphs (2) and (3) of the UUJF, and is confirmed by Constitutional Court Decision No. 18/PUU-XVII/2019 jo. No. 2/PUU-XIX/2021, which requires an agreement on breach of contract (default) and is based on a Fiduciary Certificate for the validity of parate execution, or through the courts if these conditions are not met. Such unilateral actions can be classified as unlawful acts with consequences of compensation based on Article 1365 of the Civil Code, while efforts to resolve them can be carried out through non-litigation or litigation channels if no agreement is reached. The research recommendations emphasize the importance of enforcement based on Fiduciary Certificates, compliance by Financing Companies with laws and regulations, and prioritizing dispute resolution through non-litigation means in order to maintain a balance of rights and obligations between creditors and debtors.